Bacterial c-di-GMP is an immunostimulatory molecule - Karaolis, David K R; Means, Terry K; Yang, De; Takahashi, Munehisa; Yoshimura, Teizo; Muraille, Eric; Philpott, Dana; Schroeder, John T; Hyodo, Mamoru; Hayakawa, Yoshihiro; Talbot, Brian G; Brouillette, Eric; et al. (Journal of Immunology, 2007)
Cyclic diguanylate (c-di-GMP) is a bacterial intracellular signaling molecule. We have shown that treatment with exogenous c-di-GMP inhibits Staphylococcus aureus infection in a mouse model. We now report that c-di-GMP is an immodulator and immunostimulatory molecule. Intramammary treatment of mice with c-di-GMP 12 and 6 h before S. aureus challenge gave a protective effect and a 10,000-fold reduction in CFUs in tissues (p < 0.001). Intramuscular vaccination of mice with c-di-GMP coinjected with S. aureus clumping factor A (ClfA) Ag produced serum with significantly higher anti-ClfA IgG Ab titers (p < 0.001) compared with ClfA alone. Intraperitoneal injection of mice with c-di-GMP activated monocyte and granulocyte recruitment. Human immature dendritic cells (DCs) cultured in the presence of c-di-GMP showed increased expression of costimulatory molecules CD80/CD86 and maturation marker CD83, increased MHC class II and cytokines and chemokines such as IL-12, IFN-gamma, IL-8, MCP-1, IFN-gamma-inducible protein 10, and RANTES, and altered expression of chemokine receptors including CCR1, CCR7, and CXCR4. c-di-GMP-matured DCs demonstrated enhanced T cell stimulatory activity. c-di-GMP activated p38 MAPK in human DCs and ERK phosphorylation in human macrophages. c-di-GMP is stable in human serum. We propose that cyclic dinucleotides like c-di-GMP can be used clinically in humans and animals as an immunomodulator, immune enhancer, immunotherapeutic, immunoprophylactic, or vaccine adjuvant.